Pengaruh Penambahan Atraktan yang Berbeda dalam Pakan Pasta Terhadap Retensi Protein, Lemak dan Energi Benih Ikan Sidat (Anguilla bicolor) Stadia Elver [ Effects Of Addition Different Attractants In Pasta Feed Against Retention Of Protein, Fat and Energy Eel Fish Seed (Anguilla bicolor) Stadia Elver] - Muhammad Arief; Suryo Yudiarto; Agustono Agustono (Jurnal Ilmiah Perikanan dan Kelautan, 2012)
Abstract Indonesia has a great potential for the development of eel fish (Anguilla bicolor) farming. Availability of seeds is not enough to make the farmers are interested to cultivate eel fish because fish growth is long enough. It can be addressed through accelerated consumption of feed with the proper administration of feed attractants that can spur growth. This study aimed to determine the effect of the addition of different attractants in pasta feed on the retention of protein, fat and energy of eel fish seed (Anguilla bicolor) stadia Elver. The experiment was conducted at the Faculty of Fisheries and Marine Resources, University of Airlangga. Proximate analysis of feed ingredients, fish proximate analysis of the beginning and end of the study conducted in Unit Inspection Service laboratory Consulting and Training Faculty of Veterinary Medicine, University of Airlangga. Research using a pasta feed plus attractants shrimp oil (A), eel oil (B), milkfish oil (C), squid oil (D) and without attractant (E) with the main parameters, namely retention of protein, fat and energy and support parameters that water quality, including temperature, solubility of oxygen, pH and ammonia. Analysis of data using Variety Analysis (ANOVA) and to determine the differences between treatments performed tests Distance Regression Duncan. The results showed that the addition of different attractant in feed pasta provide the best protein retention in treatment E (12.83%) and then a row followed by treatment C (11.98%), D (11.45%), B (10 , 26%) and A (7.78%). Best energy retention in treatment E (10.77%), then a row followed by treatment D (9.59%), C (9.47%), B (8.65%) and A (8.27% ). Best fat retention in treatment D (3.76%) and lowest in the C treatment (2.12%). Water quality maintenance media eel fish are temperature 28 º -28.5 º C, pH 7-8, dissolved oxygen 4-8 mg / L and ammonia from 1.5 to 2 mg / L.